Endotrophin as a risk marker of mortality and kidney complications in a type 1 diabetes cohort - Møller, Alexandra Louise; Tougaard, Ninna Hahn; Rasmussen, Daniel Guldager Kring; Genovese, Federica; Rønn, Pernille Falberg; Hansen, Tine Willum; Karsdal, Morten Asser; Rossing, Peter (Frontiers in Molecular Biosciences, 2023)
Hyperglycemia triggers pathological pathways leading to fibrosis, where extracellular matrix (ECM) components are accumulated. We investigated the potential of endotrophin, a pro-fibrotic molecule generated during collagen type VI formation, as a risk marker for complications to type 1 diabetes. Endotrophin was measured in serum and urine from 1468 persons with type 1 diabetes. Outcomes included a composite kidney endpoint, first major adverse cardiovascular event (MACE), all-cause mortality, progression of albuminuria, incident heart failure, and sight-threatening diabetic eye disease. Cox proportional hazards models adjusted for conventional risk factors were applied. A doubling of serum endotrophin was independently associated with the kidney endpoint (n = 30/1462; hazard ratio 3.39 [95% CI: 1.98-5.82]), all-cause mortality (n = 93/1468; 1.44 [1.03-2.0]), and progression of albuminuria (n = 80/1359; 1.82 [1.32-2.52]), but not with first MACE, heart failure, or sightthreatening diabetic eye disease after adjustment. Urinary endotrophin was not associated with any outcome after adjustment. Serum endotrophin was a risk marker for mortality and kidney complications in type 1 diabetes. Biomarkers of ECM remodeling, such as serum endotrophin, may identify persons with active pro-fibrotic processes at risk for complications in diabetes and where antifibrotic agents may reduce this risk.